1990
DOI: 10.1002/jbmr.5650050308
|View full text |Cite
|
Sign up to set email alerts
|

Zinc excretion in osteoporotic women

Abstract: The relation of zinc to the aging skeleton was investigated in 140 women aged 36-85 years, mostly postmenopausal, who attended the Jerusalem Osteoporosis Center. Osteoporosis was determined by lumbar spine radiograms (Smith index). Bone density (BD) of the distal radius was assessed by Compton spectroscopy and bone mineral content (BMC) at the same site by single-photon absorptiometry. Urine samples (24 h) were analyzed for zinc (UZn), hydroxyproline (UHP), calcium (UCa), magnesium (UMg), and phosphorus (UP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(39 citation statements)
references
References 35 publications
2
36
0
1
Order By: Relevance
“…Zinc deficiency is associated with skeletal growth impairment (Oner et al, 1984). It is reported to be a contributory factor in osteoporosis observed in postmenopausal women (Herzberg et al, 1990). Decrease in zinc excretion with tamarind supplementation may have a beneficial effect on the skeletal health of children from fluorotic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc deficiency is associated with skeletal growth impairment (Oner et al, 1984). It is reported to be a contributory factor in osteoporosis observed in postmenopausal women (Herzberg et al, 1990). Decrease in zinc excretion with tamarind supplementation may have a beneficial effect on the skeletal health of children from fluorotic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the activity of citrate metabolizing enzyme ACO2 is inhibited by a high level of zinc (Zn 2+ ), leading to citrate accumulation and eventual secretion into the ECM, highlighting a connection between Zn 2+ and citrate homeostasis 5. The majority of Zn 2+ in the body is stored in the skeleton and released during bone resorption 6. Furthermore, Zn 2+ acts as an activator or coactivator of a variety of proteins involved in osteogenesis including the earliest determinant of osteoblast differentiation runt‐related transcription factor 2 (Runx2) and its downstream target gene Osterix, a zinc finger motif containing transcription factor 7.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary zinc was positively correlated with serum osteocalcin in the older European adults in the present study. Some researchers have found an elevated urinary zinc excretion in osteoporotic women when compared to their age-matched controls (Herzberg et al, 1990;Szathmari et al, 1993;Relea et al, 1995). However, whether a causal relationship between urinary zinc and bone loss exists has yet to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…An inverse correlation between zinc intake and bone loss in postmenopausal women was observed by Freudenheim et al (1986). Some researchers have found an elevated urinary zinc excretion in osteoporotic women when compared to their age-matched controls (Herzberg et al, 1990;Szathmari et al, 1993;Relea et al, 1995); however, this may be related to increased bone resorption (Relea et al, 1995) leading to liberation of bone-bound zinc. More recently, Lowe et al (2002) reported that plasma zinc concentrations (as well as fractional zinc absorption) of osteoporotic elderly women were significantly (Po0.05) lower than that of young women.…”
Section: Introductionmentioning
confidence: 98%